Hydrologic resilience and Amazon productivity - Anders Ahlström (Nature Portfolio, 2017)
Earth system model simulations of future climate in the Amazon show little agreement. Here, the authors show that biases in internally generated climate explain most of this uncertainty and that the balance between water-saturated and water-limited evapotranspiration controls the Amazon resilience to climate change.